Effects of fluoride on morphology, growth, development, and thyroid hormone of Chinese toad (Bufo gargarizans) embryos. (12th October 2017) - Zhang, Yuhui; Xie, Lei; Li, Xinyi; Chai, Lihong; Chen, Mengxing; Kong, Xiaojing; Wang, Qingqing; Liu, Jingfei; Zhi, Lijuan; Yang, Chang; Wang, Hongyuan
Abstract : Excessive fluoride in natural water ecosystem has the potential to detrimentally affect amphibians, but little is known of such effects or underlying mechanisms in Bufo gargarizans embryos. In the present study, the effects of fluoride exposure on B. gargarizans embryos were investigated. First, fluoride teratogenic experiment showed that the 9 days EC50 of fluoride on B. gargarizans embryos was 177.62 mg/L. Then, we studied the sublethal effects of fluoride on B. gargarizans embryos at control, 0.7, 4.1, 19.6, 41.9, and 62.7 mg/L fluoride concentration. Malformation, growth, and development of embryos were monitored, and type 2 and 3 iodothyronine deiodinase ( Dio2 and Dio3 ), thyroid hormone receptors ( TRα and TRβ ) mRNA levels were measured. Our results showed the morphological malformations, such as tail curvature (lordosis), edema, cuticularized ciliated cells, and hyperplasia were occurred during fluoride exposure. Growth and development were all inhibited at 19.5, 41.9, and 62.7 mg/L fluoride‐treated groups after 9 days' exposure. According to real‐time PCR results, exposure to fluoride upregulated Dio3 and TRβ mRNA expression and downregulated Dio2 and TRα mRNA level. All above indicated that excessive fluoride could induce morphology malformations, inhibit embryonic growth and development, and disrupt the normal function of maternal thyroid hormone in B. gargarizans embryos. Environ. Mol. Mutagen. 59:123–133, 2018. © 2017 Wiley Periodicals, Inc.